94.0k views
5 votes
-n+(-4)-(-4n)+6


solve

User Vladan
by
5.2k points

2 Answers

6 votes
the answer is =3n+2 Hope this helps ! ;-)
User Laker
by
5.3k points
6 votes

Answer:

3n + 2

Explanation:

-n+(-4)-(-4n)+6

= -n -4 +4n +6 [positive plus negative = negative; ∴ +(-4) = -4

=4n - n +6 - 4 negative plus negative = positive; ∴ -(-4n) = 4]

now subtract n from 4n and subtract 4 from 6

=3n + 2

User Pepper
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.